1970
DOI: 10.1042/cs0380123
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Studies on Inflammation in Human Knee Joints: Xenon (133Xe) Clearances Correlated with Clinical Assessment in Various Arthritides and Studies on the Effect of Intra-Articularly Administered Hydrocortisone in Rheumatoid Arthritis

Abstract: 1. The rate of disappearance of intra-articularly administered 133Xe from the knee joint was studied in normal subjects and in patients suffering from various arthritides. The disappearance curve was monoexponential and could be described by a biological half life . The half lives were shown to be reproducible, but could be reduced marginally by aspirating knee joint effusion when present. 2. It was demonstrated that the values depended, not upon the pathological diagnosis, but upon the degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1971
1971
1987
1987

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The method of injection, with aseptic precautions, has been described previously (Dick et al, 1970a). To obtain reproducible results, it is of particular importance to ensure that the needle point is free in the joint cavity, and to wait for approximately 5 min following the insertion of the needle before injecting the isotope solution.…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
See 1 more Smart Citation
“…The method of injection, with aseptic precautions, has been described previously (Dick et al, 1970a). To obtain reproducible results, it is of particular importance to ensure that the needle point is free in the joint cavity, and to wait for approximately 5 min following the insertion of the needle before injecting the isotope solution.…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
“…The xenon 133Xe clearance technique has been employed in the study of normal and diseased joints (Dick, Whaley, St. Onge, Downie, Boyle, Nuki, Gillespie & Buchanan, 1970a) and the rate of clearance of intra-articularly injected 133Xe has been shown to be related to synovial perfusion (Dick, St. Onge, Gillespie, Downie, Nuki, Gordon, Whaley, Boyle & Buchanan, 1970b). In this study we attempt to adduce indirect evidence of the existence of adrenergic receptors in normal and diseased human synovial tissue from the effect of intra-articularly administered catecholamines on the 133Xe clearance rate.…”
mentioning
confidence: 99%
“…However, the quantitative estimation of the degree of scan positivity on different examinations would be of greater value and this is currently being investigated. Recent investigations have suggested that this is feasible (Dick, Neufeld, Prentice, Woodburn, Whaley, Nuki, and Buchanan, 1970;Dick, Whaley, St. Onge, Downie, Boyle Nuki, Gillespie, and Buchanan, 1970).…”
Section: Resultsmentioning
confidence: 99%
“…Removal of 50 ml of fluid resulted in a marked increase in clearance (decrease in Ty2s) which had actually become slower than control. 133Xe clearance became more rapid in 7 of 7 knees afflicted with rheumatoid arthritis after joint fluid aspiration in a study reported by Dick and collaborators (18). The increase was just short of statistical significance when group means were compared, but is significant if a t-test for paired observations is used.…”
Section: Synovial Blood Flowmentioning
confidence: 95%
“…There is no way to measure synovial blood flow with confidence, although St. Onge, Dick, and their collaborators have developed and used the lssXe washout technique for this purpose (17)(18)(19)(20)(21)(22). This technique was first used by Phelps and McCarty as an empirical measurement of relative blood flow in inflamed animal joints (23).…”
Section: Synovial Blood Flowmentioning
confidence: 99%